Integrating Digital Literacy in Secondary Education: A Comparative Analysis of Effective Teaching Strategies Across Asia - Apriyanto, Apriyanto; Albadri, Albadri; Hasnah, Sitti; Nugroho, Agung Yuliyanto; Smas, Musa Hefer (PT Inovasi Pratama Internasional, 2024)
This research project examines the ways in which digital literacy is incorporated into the secondary education curriculum in various Asian countries. This study aims to investigate the comparative teaching strategies employed with the aim of enhancing students' digital competencies. Qualitative research methods were employed to obtain data through in-depth interviews, document analysis and participatory observation in secondary schools in five Asian countries: Indonesia, Singapore, India, South Korea and Japan. The findings indicate that technology-based strategies, teacher training and national policies play an instrumental role in the successful integration of digital literacy. The research validates that a comprehensive approach to the incorporation of digital literacy in secondary education in Asia necessitates an interwoven combination of pedagogical strategies, conducive policies and robust technological infrastructure. The insights gained from this research are invaluable for the formulation and refinement of an inclusive and effective digital literacy curriculum.